Iron Biofortification of Myanmar Rice - Aung, May S.; Masuda, Hiroshi; Kobayashi, Takanori; Nakanishi, Hiromi; Yamakawa, Takashi; Nishizawa, Naoko K. (Frontiers in Plant Science, 2013)
Iron (Fe) deficiency causes elevates human mortality rates, especially in developing countries. In Myanmar, the prevalence of Fe-deficient anemia in children and pregnant women are 75% and 71%, respectively. Myanmar people have one of the highest per capita rice consumption rates globally. Consequently, production of Fe-biofortified rice would likely contribute to solving the Fe-deficiency problem in this human population. To produce Fe-biofortified Myanmar rice by transgenic methods, we first analyzed callus induction and regeneration efficiencies in 15 varieties that are presently popular because of their high yields and/or qualities. Callus formation and regeneration efficiency in each variety was strongly influenced by types of culture media containing a range of 2,4-dichlorophenoxyacetic acid concentrations. The Paw San Yin variety, which has a high Fe content in polished seeds, performed well in callus induction and regeneration trials. Thus, we transformed this variety using a gene expression cassette that enhanced Fe transport within rice plants through overexpression of the nicotianamine synthase gene HvNAS1, Fe flow to the endosperm through the Fe(II)-nicotianamine transporter gene OsYSL2, and Fe accumulation in endosperm by the Fe storage protein gene SoyferH2. A line with a transgene insertion was successfully obtained. Enhanced expressions of the introduced genes OsYSL2, HvNAS1, and SoyferH2 occurred in immature T2 seeds. The transformants accumulated 3.4-fold higher Fe concentrations, and also 1.3-fold higher zinc concentrations in T2 polished seeds compared to levels in non-transgenic rice. This Fe-biofortified rice has the potential to reduce Fe-deficiency anemia in millions of Myanmar people without changing food habits and without introducing additional costs.